EFEK INOKULASI ACTINOMYCETES PADA PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine Max Merril L.): Inoculation Effect of Actinomycetes in Growth and Result of Soybean Plants (Glycine Max Merril L.) - Asmiaty Sahur; Ambo Ala; Elkawakib Syam’un (Program Studi Agroteknologi Fakultas Pertanian, Peternakan, dan Kehutanan Universitas Muslim Maros, 2018)
This study was conducted in the experimental garden of the Faculty of Agriculture and Forestry, Hasanuddin University, Tamalanrea, , Makassar, from November to February 2017. This study aims to analyze the effect of application of inoculation on the growth and production of soybean plants. The study was conducted using factorial randomized block design consisting of two factors. Inoculation of Actinomyces sp (A) as the first factor consisted of without inoculation (a0), inoculation 3.25 X 107CFU / ml (a1), inoculation 3.25 x 108CFU / ml (a2). 3.25 x 109CFU / ml (a3). Inoculation of Rhizobium sp (R) as the second factor consisted of three levels, namely inoculation (r1) 4.25 x 108CFU / ml, (r2) 4.25 x 109CFU / ml, and (r3) 4.25 x 1010CFU / ml. The two factors tested shown that 12 combinations of treatments, each unit treatment were used two plants and repeated three times, so there are 72 plants were used. The inoculation of Actinomycetes and Rhizobium showed better results for the final phase of plant height, number of branches, number of root nodules, number of early phase leaves and vegetative phase, stomata density and weight of crop seeds.